[News Script: Nixon-Pompidou Meeting] - WBAP-TV (Television station : Fort Worth, Tex.) (1973)
Script from the WBAP-TV/NBC station in Fort Worth, Texas, relating a news story about a meeting between President Nixon and President Pompidou.